2001
DOI: 10.4049/jimmunol.167.12.7009
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Flagellin-Dependent Proinflammatory Responses Are Localized to the Conserved Amino and Carboxyl Regions of the Protein

Abstract: Flagellin, the monomeric subunit of flagella, is an inducer of proinflammatory mediators. Bacterial flagellin genes have conserved domains (D1 and D2) at the N terminus and C terminus and a middle hypervariable domain (D3). To identify which domains induced proinflammatory activity, r6-histidine (6HIS)-tagged fusion constructs were generated from the Salmonella dublin (SD) fliC flagellin gene. A full-length r6HIS SD flagellin (6HIS flag) induced IκBα loss poststimulation and NF-κB activation in Caco-2BBe cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 27 publications
6
104
0
1
Order By: Relevance
“…Although the TLR5 dependence of Gram-negative flagellin signaling has been well documented, the structural requirements for the interaction between flagellin and TLR5 are only partially understood. Structure/function studies with soluble flagellin indicate that the amino and carboxyl constant regions are most critical for TLR5 signaling (22,23). We have shown that flagellin is active at concentrations in the picomolar to nanomolar range (24), a finding that is consistent with a very high affinity interaction.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Although the TLR5 dependence of Gram-negative flagellin signaling has been well documented, the structural requirements for the interaction between flagellin and TLR5 are only partially understood. Structure/function studies with soluble flagellin indicate that the amino and carboxyl constant regions are most critical for TLR5 signaling (22,23). We have shown that flagellin is active at concentrations in the picomolar to nanomolar range (24), a finding that is consistent with a very high affinity interaction.…”
supporting
confidence: 68%
“…The results of two recent studies (22,23) indicate that the conserved amino and carboxyl regions of flagellin are required for biologic activity. This appears to be in conflict with our observation (24) that a peptide containing only these two regions was inactive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the motif 89 -96 is absolutely required (8 -10). The middle (outer) domain of flagellin FliC comprises amino acids from positions 170 -400 and is not mandatory for TLR5 signaling (9,10). It is designated as a hypervariable region, since the primary sequences greatly vary in composition and size from one bacterial species to another.…”
Section: Deletion Of Flagellin's Hypervariable Region Abrogates Antibmentioning
confidence: 99%
“…Recombinant flagellin of B. pseudomallei was obtained from E. coli BL21 (pGex4T-2/fliC) and the flagellin preparation was then digested with thrombin as described elsewhere (4). Any contaminating lipopolysaccharide (LPS) present in the flagellin was removed using a polymyxin B column (8) in accordance with the manufacturer's instructions (Detoxi-gel; Rockford, Ill., U.S.A.). This was repeated until the concentration of LPS was less than 1 pg/ml as determined by the Limulus Amebocyte Lysate assay (BioWhittaker, Inc., Walkersville, Md., U.S.A.).…”
Section: Methodsmentioning
confidence: 99%